Validity and reliability of the toxic leadership behaviors of nurse managers scale among Chinese nurses - Zhou, Yumei; Lin, Juanjuan; Liu, Xing; Gao, Shuping; Yang, Fang; Xu, Huili (Frontiers in Psychology, 2024)
Objectives Toxic leadership is increasingly becoming common in the nursing field, but the measurement tools are lacking. Therefore, this study aimed to translate the toxic leadership behaviors of nurse managers (ToxBH-NM) scale into Chinese and test its psychometric properties among Chinese nurses. Methods The data for this study were obtained from a cross-sectional survey of 1,195 nurses. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to examine the structural validity of the ToxBH-NM. The following psychometric properties of the scale were assessed: content validity, criterion validity, internal consistency reliability, and test–retest reliability. Results The Chinese version of the ToxBH-NM (C-ToxBH-NM) scale had two dimensions and 30 items. The correlation coefficients between the scores of each item and the total scores were 0762–0.922 (p < 0.001), and the range of the CR determination values of all the items were 8.610–18.998, with statistical significance (p < 0.001). The total content validity index (CVI) was 0.996, the average CVI was 0.996, and the item-level CVI was 0.875–1.000. Two common factors were identified in the EFA, and 81.074% of the variation was explained cumulatively. The CFA showed that all the fitting indexes reached the standard, and the model fit degree was good. When the Chinese version of the Destructive Leadership Scale was used as calibration, the correlation coefficient was 0.378 (p < 0.001). The Cronbach’s alpha coefficients of the overall scale were 0.989 and of the two dimensions were 0.969 and 0.987, respectively, with a split-half reliability of 0.966 and test–retest reliability of 0.978. Conclusion The research results show that the C-ToxBH-NM scale has good reliability and validity and can be used to evaluate the severity of toxic leadership behavior among nursing managers.